Response to periodic disturbances in the glass redraw process - Marquis, SG; O'Kiely, D; Howell, PD; Lange, U; Griffiths, IM (Springer Verlag, 2020)
The redraw process is a method employed for the manufacture of glass sheets required for example special optical filters, bendable displays, or wearable devices. During this process, a glass block is fed into a heater zone and drawn off to reduce its thickness. Fluctuations in the feed speed, the draw speed or the ambient temperature can all lead to irregularities in the final thickness profile. We present a linearized theory that allows the response to any given fluctuation to be computed, and obtain a simplified model in the high-frequency limit. The resulting framework allows for fast and efficient parameter sweeps that determine the most dangerous frequencies to be avoided and provide an important complementary tool for experimentalists working in the redraw process.